PENGGUNAAN PASIR LAUT TERHADAP KUAT TEKAN BETON KOTA BENGKULU - Redaksi Tim Jurnal (FORUM MEKANIKA, 2017)
This research was motivated by the use of sea sand to the availability of large amounts in Bengkulu city. The purpose of this study was to determine the quality of sea sand physically and to compare the compressive strength of concrete with the dunes and river sand. Sea Sand which were used in this study wereSelolongSea Sand, LakokSea Sand and Air Padang Sea Sand. The specimens were the cubical size 15 cm x 15 cm x15 cm of 40 samples with 2 types of treatment namely salt water and fresh water treatment. The planning of concrete used 0,5fasand 60-100 mmslump, The testing was done at 28 days. The result of this study showed that for doing the inspection of sand quality physically, all the tests fulfilled the requirement setexcept in the inception of sieve analysis for Air Padang sea sand, which has a very fine grain. The highestincreased of concrete compressive strength was atLakok Sea Sand, which was 3.86% of the dunes, and 4.77% for the treatment of river sand for freshwater. For the treatment of Lakoksalt water on the dunes increased to 2.22% and on the river sand increased 3.74%. Air Padang Sea Sand has the biggest reduction the compressive strength of concrete, most notably in the treatment of fresh water on the dunes of 10.33% and 9.54% of the river sand. For salt water treatment, Air Padang Sea Sand had a greater reduction which was 14.61% of the dunes and 13, 33% of the river sand.